Sustainable Development: Looking at the Gunong Kleng Village Government Strategy in Implementing Sustainable Development in Meureubo District, Aceh Barat Regency - Fhanny Inanyah; Vellayati Hajad (Ilomata International Journal of Social Science, 2022)
The purpose of this study was to find out how the strategy carried out by the Gunong Kleng Village Government was running optimally in order to implement sustainable development in the village. In carrying out development, a good plan or strategy is needed so that the implementation can be beneficial for the community and continue to be sustainable. The Gunong Kleng Village Government has carried out various strategies to maximize development in the village by: first, increasing the capacity of Human Resources (HR) through the provision of guidance, holding courses or training, and competencies that can increase the knowledge of the village community. Second, monitoring and evaluation of the ongoing program is carried out in order to achieve the expected target. Third, the provision and improvement of complete facilities and tools to manage available natural resources. The methodology used is a qualitative method with a descriptive approach, with data collection techniques using the methods of observation, interviews, and documentation. Based on the results of the research conducted by the researchers concluded that development in Gunong Kleng Village has not run optimally as planned in the village RKPG, due to the lack of community awareness, especially in terms of economic improvement and village community empowerment. In addition, community participation and lack of interest from the community itself.